A systematic method for hypermedia usability inspection - Garzotto, F.; Matera, M. (The new review of hypermedia and multimedia, 1997)
This paper will discuss a usability inspection method for hypermedia applications, that explicitly takes into account the particular features of this class of systems. The proposed technique is a specialisation for hypermedia of a general methodology for usability evaluation of interactive systems, named SUE -Systematic Usability Evaluation. Our approach aims to support a systematic evaluation process, making it well organised, fast and cheap, and is based on the use of a hypermedia model, a set of hypermedia-specific usability attributes, and a set of patterns of inspection activities, called abstract tasks. The model identifies the 'dimensions' along which hypermedia usability can be analysed, defines the application constituents that must be inspected, and allows a precise formulation of usability attributes and abstract tasks. Abstract tasks provide operational guidelines for systematically checking usability attributes throughout the application. To exemplify our approach, we will report some inspection results concerning nine commercially available hypermedia CD-ROMs